Model of tariff regulation of natural monopolies in the context of taking into account consumer choice - K. A. Kudryavtsev (Модернизация, инновация, развитие, 2024)
Purpose: is to develop the menu of contracts for the model of tariff regulation of natural monopolies in the areas of heat supply, water supply and sanitation, to ensure the economic security of subjects of the tariff regulation system.Methods: the article uses a systematic approach. The theoretical basis of the study is the synthesis of the theory of tariff regulation, the theory of contracts and the theory of economic security. The work also applies special methods used in calculating tariffs: economically justified costs (expenses) and tariff indexation.Results: the presented study substantiates the model of tariff (antimonopoly) regulation of subjects of natural monopolies, taking into account their economic security. Using the provisions of the contract theory, a new menu of contracts for consumers has been developed and tested, allowing them to be included in the process of influencing the size of tariffs, stimulating demand, taking into account low-level indicators in tariff regulation and solving the problem of fulfilling the production programs of monopolists.Conclusions and Relevance: existing practical and theoretical models of tariff regulation do not ensure the economic security of natural monopolies and consumers. In this regard, a substantiation of the model of tariff (antimonopoly) regulation of subjects of natural monopolies and the development of a new menu of contracts for consumers, providing for their choice of one of two types of contracts, were made. The main conclusions of the study can be used to improve the state tariff policy.